Validasi Metode Spektrofotometri UV Untuk Penetapan Kadar Kolkisin Dalam Infus Kembang Sungsang - Muhammad Muslich; Isnaeni Isnaeni; Sudjarwo Sudjarwo (Berkala Ilmiah Kimia Farmasi, 2020)
Validation of colchicine analysis methods in herbal infusions has been carried out to facilitate quality control of raw materials or simplicia. The validation parameters of the method set include selectivity, linearity, precision, and accuracy, which are included in category I. In this study, the raw material was prepared from the leaves of Gloriosa superba Linn. infusion made. The results of the selectivity test with colchicine as a standard provide uptake at a chosen wavelength of 340.2 nm. Linearity test results show the equation y = 0.0303x + 0.0131 with r = 0.9998> r Table for n = 6, ie 0.917 for p <0.01 and 0.811 for p = <0.05, the value of Vxo is 1 15%. In the precision test, the coefficient of variation is 0.54% and the accuracy test gives an average recovery of 92.81% ± 4.16%. Determination of colchicine in the infusion preparation was carried out as many as three replications. The results showed that the content of colchicine in raw materials was 0.3152% ± 1.99%, while the colchicine content in herbal infusion preparations was 0.483 ± 4.47%.